Performance Evaluation of Passive Cavitation Mapping for Estimating Ultrasound-Induced Cavitation Dose - Tran, Megan YanYan Banh (University of Waterloo, 2023)
The development of targeted drug delivery technologies to increase the specificity and efficacy of cancer treatments and reduce the reliance on systemic chemotherapy drugs have long been areas of research. Recent advances in therapeutic ultrasound have shown that targeted, enhanced drug uptake can be achieved using ultrasound-mediated microbubble cavitation, a non-invasive drug delivery scheme which leverages the mechanical effects of microbubble cavitation to increase vascular permeability. Spatiotemporal measurement and control of cavitation activity are needed to ensure that only the desired bioeffects (e.g., increased drug penetration) are induced, and the harmful ones (e.g., hemorrhage) are avoided. However, many of the current passive cavitation mapping (PCM) methods lack a standard, system-independent measure of cavitation dose, which impedes the generalizability of research into cavitation-bioeffects relationships. In this thesis, we propose an experimental platform and comparative study that enables us to evaluate the accuracy and performance of PCM methods end-to-end. The experimental platform was designed to allow for the codetection of a microbubble cavitation target with both an ultrasound array (for PCM) and a hydrophone, which provided an independent reference measurement of cavitation energy (dose). In the comparative study, four popular PCM methods whose absolute cavitation dose magnitudes have not all previously been compared were implemented. Cavitation maps for different frequency bands corresponding to different types of cavitation activity were generated for each input pressure and analyzed for dose accuracy and spatial performance. The key result from the analysis revealed biases and variations in cavitation dose estimation that were both method-specific and frequency-dependent. Additionally, the extracted cavitation dynamics and spatial performance aligned with previous work, validating the experimental platform for simultaneous testing of dose accuracy and spatial performance. These findings confirm that PCM-induced dose bias needs to be accounted for in cavitation dose reporting. Overall, the proposed method was able to quantify differences in cavitation dose accuracy of PCM methods, the first step needed toward the goal of standardizing cavitation dosimetry, which can potentially allow for the smoother clinical translation of cavitation-mediated therapies.
Keywords: therapeutic ultrasound; ultrasound imaging; passive cavitation mapping